2016
DOI: 10.1186/s13071-016-1647-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of real-time PCR assays for evaluation of immune response and parasite load in golden hamster (Mesocricetus auratus) infected by Leishmania (Viannia) braziliensis

Abstract: Background: Cutaneous leishmaniasis (CL) is a neglected disease with a broad spectrum of clinical manifestations, ranging from small cutaneous nodules to severe mucosal tissue destruction. Leishmania (Viannia) braziliensis is the main species attributed to CL in the Americas. However, studies of experimental infection are limited in the murine model due to the self-resolutive pattern of the disease. Previously, our group demonstrated that the hamster model reproduces many of the clinical and histopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The results of the present study are consistent with those of Bayraktar et al [32] and Ribeiro-Romão et al [22] as we found that the recorded profile of cytokines revealed the presence of a mixed type of immune response (Th1 and Th2 cytokines) and the dominant production level related to Th1 cytokines (IFN-γ and TNF-α). A study conducted by Singer and Nash [7] disagreed with our results as they reported that neither a specific Th1 nor a specific Th2 response seem to be necessary for giardiasis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study are consistent with those of Bayraktar et al [32] and Ribeiro-Romão et al [22] as we found that the recorded profile of cytokines revealed the presence of a mixed type of immune response (Th1 and Th2 cytokines) and the dominant production level related to Th1 cytokines (IFN-γ and TNF-α). A study conducted by Singer and Nash [7] disagreed with our results as they reported that neither a specific Th1 nor a specific Th2 response seem to be necessary for giardiasis.…”
Section: Discussionsupporting
confidence: 93%
“…In line with the evaluation of the immune response, the use of a reproducible, efficient and fast method to provide this precise assessment is extremely beneficial. Quantitative real time-PCR has been considered by many authors to be of great benefit for assessment of immune responses in giardiasis [18][19][20][21] and leishmaniasis [22] ; and is of greater sensitivity than many other procedures [23] . Despite all efforts made on this issue, the available knowledge about the mechanisms of the immune response to giardiasis is still unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be due to technical errors in sampling of the tissue and/or processing of the PCR. On the other hand, it is worth mentioning that the sensitivity of PCR for detection of leishmaniasis is not perfect [ 96 ]. Four patients out of 33 in group A and one out of 29 patients in group B (a total of 5 patients with PCR-undetected strains of Leishmania) , had complete cure in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA concentration obtained from the extraction was 9.1 ng/μL determined using the Qubit Fluorimeter ® . The Leishmania standard curve was built from 10-fold serial dilutions ranging from 1.0 x10 4 to 1.0 x10 -2 parasite DNA equivalents/reaction [ 12 ].…”
Section: Methodsmentioning
confidence: 99%